Metal trace determination in seawater samples from Antarctica - II - MENTASTI, Edoardo; PORTA, Valerio; ABOLLINO, Ornella; SARZANINI, Corrado (1991)
A series of metal ion traces, in Antarctic Seawater (Ross Bay), have been determined using ICP atomic emission spectroscopy. In order to obtain the sensitivity required, enrichment procedures based on precomplexation/adsorption on a minicolumn have been optimized and adopted. Such procedures allow a closed-loop on-line treatment of the sample which ensures very limited alteration of the sample. For the retention of metal traces, 8-hydroxyquinoline (8-Oxine) or 1-(2-thiazolylazo)-2-naphthol (TAN) were used in conjunction with Amberlite XAD-2 resin. Precision, accuracy, blanks and detection limits of the procedures optimized are discussed.